Data Integration Techniques For Healthcare ? A Comprehensive Survey - Thirumahal, R; Sudha Sadasivam, G (International Journal of Computer Sciences and Engineering, 2020)
Data is the most valuable asset. As a strategy, integration is the first step towards transforming data into meaningful and valuable information. Data integration provides the ability to manipulate data transparently across multiple data sources. Healthcare sector in particular has been hindered by the diversity of the biomedical data. A framework to unify the sources of such diverse data can facilitate diagnosis and plan for treatment. According to Experian, 66% of companies lack a centralised approach to data resulting in data silos. The data integration market is expected to grow annually at the rate of 12.5% since 2018. This paper discusses the need for data integration, the challenges in implementing a data integration framework, various approaches for data integration, their strength and weakness. The research directions which act as additional add-on or improvements to the existing system have been discussed.